2008
DOI: 10.1038/clpt.2008.172
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in the CYP2D6 Gene Is Associated With a Lower Heart Rate and Blood Pressure in β-Blocker Users

Abstract: Several beta-blockers are metabolized by the polymorphic enzyme cytochrome P450 2D6 (CYP2D6). CYP2D6*4 is the main polymorphism leading to decreased enzyme activity. The clinical significance of impaired elimination of beta-blockers is controversial, and most studies suffer from inclusion of small numbers of poor metabolizers (PMs) of CYP2D6. In this study, the association between CYP2D6*4 and blood pressure or heart rate was examined in 1,533 users of beta-blockers in the Rotterdam Study, a population-based c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
107
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(121 citation statements)
references
References 19 publications
8
107
1
2
Order By: Relevance
“…19 Three of the studies were conducted primarily in individuals with hypertension, 15,20,21 one was in patients treated for acute myocardial infarct, 22 whereas one was a population-based study in which the indication was not mentioned. 23 Concentrations of the active S-enantiomer were measured in two of the studies 15,19 and intergenotype differences in S-metoprolol concentrations were observed, although these were not as marked in extent as in our study.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…19 Three of the studies were conducted primarily in individuals with hypertension, 15,20,21 one was in patients treated for acute myocardial infarct, 22 whereas one was a population-based study in which the indication was not mentioned. 23 Concentrations of the active S-enantiomer were measured in two of the studies 15,19 and intergenotype differences in S-metoprolol concentrations were observed, although these were not as marked in extent as in our study.…”
Section: Discussionmentioning
confidence: 59%
“…In the three studies mentioned above [21][22][23] that showed greater clinical effects in patients with no functional alleles, there was also some evidence of greater effects in patients with a single functional allele. Rau et al 21 stated that although it was not a specific aim of the study, a significant trend for a greater decrease in heart rate and diastolic blood pressure was seen from EMs through IMs to PMs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5-10 % av personer av kaukasisk (vesteuropeisk) avstamning har en homozygot defekt i CYP2D6-funksjonen og er såkalte langsomme omsettere. Disse har en økt risiko for bivirkninger, spesielt bradykardi, ved bruk av anbefalte doser metoprolol (2,3). For den resterende delen av befolkningen -de som har funksjonell CYP2D6-metabolisme -innebaerer bruk av metoprolol sammen med legemidler som hemmer CYP2D6, en risiko for forhøyet plasmakonsentrasjon av metoprolol og økt fare for bivirkninger.…”
Section: Sammendragunclassified